Democratic development and credit: "Democracy doesn't come cheap" But at least credit to its corporations will be - Manthos D. Delis; Iftekhar Hasan; Steven Ongena (Bank of Finland, 2018)
Does democratization reduce the cost of credit? Using global syndicated loan data from 1984 to 2014, we find that democratization has a sizeable negative effect on loan spreads: a one-point increase in the zero-to-ten Polity IV index of democracy shaves at least 19 basis points off spreads, but likely more. Reversals to autocracy hike spreads more strongly. Our findings are robust to the comprehensive inclusion of relevant controls, to the instrumentation with regional waves of democratization, and to a battery of other sensitivity tests. We thus highlight the lower cost of loans as one relevant mechanism through which democratization can affect economic development.
URN:NBN:fi:bof-201810112085
Keywords: G21; G30; P16; P26; P27; P47; 330